Determining the starting time of car movement to stabilize the internal pressure and the temperature in the tires - Karpenko, V. O.; Kaps’kyy, D. V.; Rudenko, N. V.; Neskreba, E. Ye.; Карпенко, В. О.; Капський, Д. В.; Руденко, Н. В.; Нескреба, Е. Є. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. The problem of road safety does not lose its relevance in our time. The condition and performance of tires has a significant impact on the safety of road transport. Unfortunately, the tire pressure monitoring requirements of the developers are not always met. Naturally, now some modern cars are equipped with various systems for monitoring and even adjusting the internal tire pressure. However, there are relatively short periods of time during which the pressure and temperature in the tire change dramatically, and hence its other performance and properties. First of all, we are talking about dramatically changing weather conditions and the starting movement of the car. And then additional monitoring of tire pressure is needed. Goal. On the basis of the experimental studies carried out, to obtain the dependence of the tempera-ture and pressure changes inside the tire on the time of car movement. To determine the initial period of time of car movement until the pressure and temperature in the tested tires stabilize. Methodology. The work used the technique of both bench tests of tires in the laboratory and road tests under real weather conditions by car. Based on the numerical processing of the ex-perimental results, dependencies were obtained, using which it is possible to determine the in-crease in temperature and pressure in tires in the mode of starting movement of the car. Results. The analysis of scientific publications on this topic is performed. The time from the beginning of the car to the stabilization of temperature and internal pressure in the tires is determined, as well as the increase in temperature and pressure inside the tire during this period. The method of determining the starting time of the car to stabilize the internal pressure and temperature is proposed. Originality. In this work, for the first time, a method is proposed for assessing the temperature and internal pressure in tires in the mode of starting movement of the car, which makes it possible to obtain dependencies without resorting to further experimental studies. Prac-tical value. Using the obtained dependencies for certain tires and under different weather condi-tions, it is possible to predict the change in tire pressure at the starting mode of the car's movement, and therefore make adjustments to this value, if necessary, which will have a positive effect on the safety of moving vehicles.
Keywords: car tire; stability; vehicle steerability; safety; stabilization; pressure; temperature; автомобільна шина; стійкість; керованість; безпека; стабілізація; тиск; температура; 629.341; 10.30977/AT.2219-8342.2021.48.0.38